PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 5 PEMATANGSIANTAR - Felix Aryanto Hutabarat; Injen Pardamean Butarbutar; Tumpal Manahara Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem in this study is the low economic learning outcomes of students in the learning process. This study aims to determine the improvement of economic learning outcomes on the subject of monetary economic policy and fiscal economic policy of class Xl SMA Negeri 5 Pematangsiantar Learning Year 2023-2024 by applying a jigsaw type cooperative learning approach.This type of research is Classroom Action with quantitative methods Pretest and Post-test. The population of this study was class XI SMA Negeri 5 Pematangsiantar which amounted to 175 people. Based on purposive sampling technique, the researcher took the research sample is 2 classes, namely class XI IPS 1 (experimental class) and class XI IPS 2 (control class) which amounted to 71 people. Data collection techniques in the study using pretest without applying the jigsaw type cooperative learning model and posttest by applying the jigsaw type cooperative learning model to the experimental class. The results of the average value of the pretest namely class XI IPS 1 66.29 and XI IPS 2 44.72. Then the results of the average value of the post-test is XI IPS 1 79.14 and XI IPS 2 70.27. Based on the results of data analysis and hypotheses tested, that the jigsaw type cooperative learning model affects student learning outcomes.Based on the statistical hypothesis test with paired samples test, the significance value is 0.000 <0.05 in the sense that the calculated statistical results (t output number) < table statistics (t table) it is concluded that H0 is rejected and H1 is accepted. Thus the Jigsaw Type Cooperative learning model affects the learning outcomes of students in class Xl SMA Negeri 5 Pematangsiantar.